Food sovereignty: a look from the beginning of the best interests of the child in Ecuador - Dueñas, Ana Elizabeth (Frónesis, 2022)
Food policies for the benefit of children and adolescents are analyzed through the actions of food sovereignty established in Ecuador, taking into consideration the criteria established by the principle of superior interest to materialize the human right to food that promotes proper nutrition of these by virtue of of the alarming figures recorded by the National Institute of Statistics and Censuses for 2014, where a quarter of the population under 2 years of age (24.8%) presented chronic malnutrition, which affects cognitive, affective and social development of early childhood. The methodology used is of the documentary-bibliographic type through the analysis of legal and doctrinal sources, and of the documents containing the public policies of the State under the inductive-deductive method. The results allow estimating that the recognition of the rights of the child generates an important guarantee against the action of the State and represents a duty of the public powers to attend to the satisfaction of these rights as stipulated in the Agenda 2030 of the General Assembly of the United Nations Organization through its 17 objectives. It is concluded that the State, within the framework of food sovereignty, is obliged to implement public policies guaranteeing the priority protection of the child and adolescent population, recognizing their human dignity and the urgent need to ensure their protection, development and survival. For this, it is imperative to articulate all the objectives, goals and strategies with the criteria of the principle of the best interests.